A novel Kriging-median inverse compensator for modeling and compensating asymmetric hysteresis of pneumatic artificial muscle. (18th October 2018) - Yang, Hui; Chen, Yang; Sun, Yao; Hao, Lina
Abstract: McKibben muscle is a kind of pneumatic artificial muscles (PAMs), and has been widely applied on robotic field as an actuator. Nevertheless, because of friction and elastic deformation, it has a strong asymmetric hysteresis which effects its actuating performance. In this paper, a novel Kriging prediction model (KPM) is proposed for describing PAM hysteresis. For improving predictive accuracy, a median filter is introduced and follows KPM, which is named Kriging-median inverse compensator (KMIC). Combining with PID controller, we present a KMIC-PID controller which consists of an open-loop KMIC and a close-loop PID controller. In order to verify the compensation control performance, some simulations and experiments are done, and the results are compared with traditional PID controller. Moreover, we introduce a Kalman filter during the experimental process, so that the effect of sensor noise can be eliminated. The Kalman filter is based on PID control parameters, so the controller used in experiment are named KMIC-Kalman PID (KPID). The simulation and experiment results show that the proposed controller has a significant compensation effect for PAM hysteresis in the condition of low frequency signal, because the hysteresis belongs to static characteristic. Furthermore, KMIC-KPID controller restricts the effect of sensor noise, which increases robustness of the system.